Pedagogical Approaches and Teaching Strategies Used in Nursing Education to Teach Academic Writing: A Scoping Review - McCloskey, Rose; Morris, Patricia; Keeping-Burke, Lisa; McGill, Ali; Goudreau, Alex; Knight, Holly; Buckley, Sarah; Mazerolle, Dave; Jones, Courtney (Quality Advancement in Nursing Education / Avancées en formation infirmière, 2025)
Academic writing is considered an essential skill in post-secondary education in general and in nursing specifically (Mitchell et al., 2020). The importance of writing for future nurses is reflected in the Canadian Association of Schools of Nursing (CASN) National Nursing Education Framework’s standards. This national consensus-based framework outlines the expectations of undergraduate nursing programs and graduates according to the six domains of knowledge, research skills and critical inquiry, nursing practice, communication and collaboration, professionalism, and leadership (CASN, 2022). Academic writing is embedded in each of these domains, as it provides students with a venue to share factual knowledge, demonstrate critical thinking, and make important connections between theory and practice (Naber & Wyatt, 2014). A scoping review of research on the pedagogical approaches and teaching strategies used to teach academic writing in nursing education yielded 12 studies. Findings show a range of approaches with varying degrees of success. Further research is needed on how best to guide and assess students’ writing.